2012
DOI: 10.1186/1471-2458-12-592
|View full text |Cite
|
Sign up to set email alerts
|

The development of the Be Active & Relax “Vitality in Practice” (VIP) project and design of an RCT to reduce the need for recovery in office employees

Abstract: BackgroundThere is strong evidence to suggest that multiple work-related health problems are preceded by a higher need for recovery. Physical activity and relaxation are helpful in decreasing the need for recovery. This article aims to describe (1) the development and (2) the design of the evaluation of a daily physical activity and relaxation intervention to reduce the need for recovery in office employees.Methods/DesignThe study population will consist of employees of a Dutch financial service provider. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 74 publications
(70 reference statements)
0
30
0
Order By: Relevance
“…29 In a 2×2 factorial design, departments received either the social environmental intervention (A), the physical environmental intervention (B), both interventions (AB), or were part of the control group (no intervention). Details of the RCT and the development of the intervention program have been reported elsewhere.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 In a 2×2 factorial design, departments received either the social environmental intervention (A), the physical environmental intervention (B), both interventions (AB), or were part of the control group (no intervention). Details of the RCT and the development of the intervention program have been reported elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, the financial service provider's main focus was on the individual level (eg, providing dietary advice, physiotherapy, and in company fitness facilities). Previous research has shown that changes in the physical environment of the worksite are expected to influence employees' attitudes, 23 job satisfaction, comfort, 24 and performance [25][26][27][28] (for more details on the intervention development, see Coffeng et al 29 ). A blueprint of the environmental interventions was developed in close cooperation with the employees, combining scientific evidence with practice-based information of the target population.…”
mentioning
confidence: 99%
“…It is well recognised that this may contribute to burnout and the literature suggests that approximately one third of cancer workers exhibit symptoms of burnout, core features of which are emotional exhaustion and disengagement (Girgis et al, 2009;Poulsen et al, 2011;Shanafelt et al, 2006). Burnout and work stress are negatively correlated with employees' health and well being and are positively associated with high desire to leave the organisation (Coffeng et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…An American study with 412 workers aged 19-63 found that the prevalence of overweight was 31% in this population 23 . Lower prevalences of overweight workers may be found in studies that emphasize interventions focused on motivating workers to perform physical activity outside the workplace 24 . Men were more likely to develop overweight.…”
Section: Discussionmentioning
confidence: 99%